Effects of submarine-cable types and parameters on performance of a future-scheduled offshore wind farm connected to Taiwan power system - Li Wang; Kuan Bing-Lin; Yu Chien-Hsiang; Wu Hong-Yi; Zeng S.- Y.; Prokhorov A. V. Anton Viktorovich; Mokhlis Hazlie; Huat Chua Kein (2020, 2020)
Title screen